2015
DOI: 10.1371/journal.pone.0134879
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation Studies of dTTP Binding and Catalysis Mediated by YhdE Dimerization

Abstract: YhdE is a Maf-like (multicopy associated filamentation) protein that primarily acts as dTTPase to hydrolyze dTTP into dTMP and two phosphate molecules in cell metabolism pathway. Two crystal structures of YhdE have been previously determined, representing the open and closed active site conformations, respectively. Based on the structures, we have carried out molecular dynamics simulations and free energy calculations to investigate dTTP binding to and hydrolysis by YhdE. Our results suggest that YhdE closed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Although the mode of dimerization is different for YjjX (PDB code: 1U5W), Mj0226 (PDB code: 1B78), and Maf (PDB code: 1EXC) possibly because of different substrate specificities, the overall structures of the monomers are very similar. All the three proteins are nucleotide binding proteins . Comparison of their active sites, suggested that there is similar loop in all proteins, which might possibly play an important role in nucleotide binding …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the mode of dimerization is different for YjjX (PDB code: 1U5W), Mj0226 (PDB code: 1B78), and Maf (PDB code: 1EXC) possibly because of different substrate specificities, the overall structures of the monomers are very similar. All the three proteins are nucleotide binding proteins . Comparison of their active sites, suggested that there is similar loop in all proteins, which might possibly play an important role in nucleotide binding …”
Section: Resultsmentioning
confidence: 98%
“…All the three proteins are nucleotide binding proteins . Comparison of their active sites, suggested that there is similar loop in all proteins, which might possibly play an important role in nucleotide binding …”
Section: Resultsmentioning
confidence: 98%
“…Enzymatic analysis by PPi fluorescence sensor shows the apparent K m of YhdE_E33A with dTTP is similar to that of wild-type YhdE, which indicates that Glu33 is probably not directly involved in dTTP binding. To help understand the hydrolysis mechanism of YhdE, we previously crystallized YhdE_E33A in the absence and presence of dTTP through co-crystallization 6 , 30 . Unfortunately, dTTP was not found in the YhdE_E33A structure from the co-crystallization, which is now not surprising because of the residual weak activity seen using our new PPi probe.…”
Section: Resultsmentioning
confidence: 99%
“…YhdE and its mutant were expressed and purified as described before 6 , 30 . The crystallization condition of the YhdE_E33A mutant included 0.1 M Tris (pH 8.0), 27% PEG 2000 MME and crystals were grown at 291 K for about two weeks.…”
Section: Methodsmentioning
confidence: 99%
“…34,53 For the binding free energies, it is made up by molecular mechanics (MM), electrostatic contributions to solvation, and nonpolar contributions to solvation. 54 In this process, the binding free energy of protein-ligand in the solvent was computed as:…”
Section: Binding Free Energiesmentioning
confidence: 99%